2018
DOI: 10.1002/aelm.201800243
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Transparent Conductive Film with Flexible Silver Nanowires Using Roll‐to‐Roll Slot‐Die Coating and Calendering and Its Application to Resistive Touch Panel

Abstract: A transparent conductive film incorporating silver nanowires (AgNW TCF) is fabricated through roll‐to‐roll (R2R) slot‐die coating and a subsequent calendering process and applied to a resistive touch panel. To produce a uniform AgNW film on a flexible polyethylene terephthalate substrate, the R2R slot‐die coating is optimized in terms of the solvent, concentration, and flow rate of the AgNW solution, and the length of the AgNWs synthesized using a polyol method. The coated AgNW TCF is calendered between two ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 45 publications
0
46
0
Order By: Relevance
“…The temperatures of the curved TFHs were measured by means of a thermocouple that directly touches on the surface of TFHs and an IR thermal image cameral (A35sc, FLIR). Figure 2a shows the contact angle of water and isopropyl alcohol (IPA) on a SiO 2 /invar substrate, since water is less affinitive than the IPA solvent on the SiO 2 coated invar substrate, the water based-Ag NWs layer is easily agglomerated before evaporation water solvent, leading to ununiform coating of Ag NW layer [38]. However, IPA and water mixed solvent based Ag NW showed a uniform coating due to lower contact angle (14.9 • ) than that (27.6 • ) of water based Ag NW ink.…”
Section: Methodsmentioning
confidence: 99%
“…The temperatures of the curved TFHs were measured by means of a thermocouple that directly touches on the surface of TFHs and an IR thermal image cameral (A35sc, FLIR). Figure 2a shows the contact angle of water and isopropyl alcohol (IPA) on a SiO 2 /invar substrate, since water is less affinitive than the IPA solvent on the SiO 2 coated invar substrate, the water based-Ag NWs layer is easily agglomerated before evaporation water solvent, leading to ununiform coating of Ag NW layer [38]. However, IPA and water mixed solvent based Ag NW showed a uniform coating due to lower contact angle (14.9 • ) than that (27.6 • ) of water based Ag NW ink.…”
Section: Methodsmentioning
confidence: 99%
“…These sensor arrays can be fabricated by the capacitive, resistive, triboelectric, or optical principles. However, many studies demonstrated the capacitive or resistive sensor arrays are best suited for multi-touch surfaces [26][27][28].…”
Section: Piezoelectric and Triboelectric Touch Sensorsmentioning
confidence: 99%
“…In addition to the semiconducting layers, highly conducting films/metal electrodes are equally crucial for realizing highly efficient, flexible, and long lifetime OLEDs. Slot-die coated metal electrode has been used in various organic devices such as photovoltaics 96,97 , sensors 98 , and touch panels 99,100 . However, it is essential to mention that there has been little progress in examining the slot-die coated anode/cathode for OLED applications.…”
Section: Coating Of Metal Electrodesmentioning
confidence: 99%